MEANS OF EDUCATIONAL INFLUENCES CONCERNING THE PHYSICAL ACTIVITY OF STUDENTS (Education in the 21st Century, 2023)
The article discusses the factors contributing to the increase in the level of physical and sports literacy and education of students. For the formation of physical culture of a person, the process of physical education is important, which in the context of general sports training should also include elements of increasing its theoretical training. The article emphasizes the fact that physical culture for a person can become a common cultural-real environment. It is concluded that if students use sporting achievements consciously and in accordance with its goals, needs and interests, then it will be possible to speak of a positive trend.